Regional differences of hepatitis B discrimination in rural China - Jun Li; Jian Wang; Stephen Nicholas; Elizabeth Maitland; Teng Fei (Taylor & Francis Group, 2021)
Background: Hepatitis B (HB) is the most serious and common viral hepatitis in China. Previous studies on HB discrimination mainly have focussed on stratified analysis, and there has been no consideration of the impact of geographical-environmental factors on HB discrimination from a spatial perspective. Objective: This study conducted a large nationwide village-based survey to test whether there were significant regional differences in HB discrimination, and to explore the relationship between different socio-economic geographical factors and HB discrimination. Methods: The sample comprised 22618 rural adults, aged over 18 years old, from villages in seven provinces, representing central, southern, and eastern coastal regions of China. Using face-to-face interviews, we surveyed participants' discrimination against HB patients or carriers. Chi-square tests were used to analyze the effects of the region on differences in proportions between three discrimination levels (low, medium, and high). A geographical detector was used to explore the relationship between different socio-economic and geographical-environmental factors and HB discrimination. Results: The distribution of HB discrimination levels across the 42 villages was statistically significant. The level of HB discrimination in the central and southern regions was generally low, and the level of HB discrimination in the eastern coastal regions was higher. Both socio-economic and geographic-environmental factors had a significant relationship with HB discrimination. Most of these relationships were not linear. Conclusions: Developing the economy and accelerating urbanization did not automatically eliminate discrimination against HB. We recommend government HB publicity and education campaigns to inform the population of HB causes and effects, and strengthen the education of students so that they can have a clear and correct understanding of HB from a young age, both of which will address HB discrimination.